Relationship betweeen the amount and location of macrophages and clinical outcome: subanalysis of the CLIMA-study. (1st January 2022) - Gatto, Laura; Alfonso, Fernando; Paoletti, Giulia; Burzotta, Francesco; La Manna, Alessio; Budassi, Simone; Biccirè, Flavio Giuseppe; Fineschi, Massimo; Marco, Valeria; Fabbiocchi, Franco; Vergallo, Rocco; Boi, Alberto; et al.
Abstract: Background: The ability of optical coherence tomography (OCT) to recognize intraplaque macrophage infiltration is now well acknowledged. This post-hoc analysis of the CLIMA study aimed to address the clinical impact of the circumferential extension of OCT-defined macrophages and their location at one year follow-up. Methods: The multicentre CLIMA study enrolled 1003 patients undergoing OCT evaluation of the untreated proximal left anterior descending (LAD) coronary artery. Measurements of circumferential extension of macrophages and measurements of the distance from intima-lumen contour to macrophages string were performed at the plaque cross-section judged as containing the greatest amount of macrophages. The main study endpoint was a composite of cardiac death, myocardial infarction (MI) and/or target vessel revascularization (TVR). Results: Patients with large macrophage arc (p = 0.001) and superficial macrophage arc (p < 0.001) showed a higher one-year incidence of the main one-year composite endpoint. Consistently hypertension (p = 0.018), family history of CAD (p = 0.046), diabetes mellitus (p = 0.036), lower ejection fraction (p = 0.009) and chronic kidney disease (p = 0.019) were more frequently found in patients experiencing the main composite endpoint. At multivariate Cox regression analysis, fibrous cap thickness < 75 μm (HR 2.51, 95% 1.46–4.32), presence of large (HR 1.97, 95%CI 1.16–3.35, p = 0.012) and superficial (HR 1.72, 95%CI 1.02–2.90; p = 0.040) macrophage arc remained independent predictors of the main composite endpoint. Large macrophage arc was associated with target LAD related MI. Conclusion: The present post-hoc analysis of the CLIMA showed that the circumferential extension of macrophages and their location are related to a composite endpoint of cardiac death, MI and/or TVR. Highlights: Patients with intraplaque macrophages have higher risk of 1-year cardiac mortality. Patients with large/superficial macrophage arc suffer more from 1-year cardiac events. Large macrophage infiltration is associated with 1-year target LAD related MI.